2004
DOI: 10.1021/ma035337a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Formation of Poly(phenylsilsesquioxane)

Abstract: Poly(phenylsilsesquioxane) with molecular weight of 1400 was synthesized by hydrolysis of phenyltrichlorosilane, followed by condensation of the resulting hydrolyzates in the presence of a catalytic amount of hydrochloric acid in methyl isobutyl ketone. The progress of dehydration of the hydrolyzates leading to poly(phenylsilsesquioxane) was monitored by 29 Si NMR spectroscopy. Dehydration of cis-(1,3,5,7-tetrahydroxy)-1,3,5,7-tetraphenylcyclooctasiloxane as a model compound was also investigated by the 29 Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 11 publications
3
37
0
Order By: Relevance
“…4 (Ph-Si(OSi-) 3 ) [10]. This further confirmed the ladder structure formation in re-precipitated polymer.…”
Section: Synthesis Of Alkali Soluble Oligo-ladder Phenylsilsesquioxansupporting
confidence: 75%
“…4 (Ph-Si(OSi-) 3 ) [10]. This further confirmed the ladder structure formation in re-precipitated polymer.…”
Section: Synthesis Of Alkali Soluble Oligo-ladder Phenylsilsesquioxansupporting
confidence: 75%
“…1 H NMR and 13 C NMR spectra were obtained on a Bruker Avance500 spectrometer (Bruker Biospin, Rheinstetten, Germany), in CDCl 3 or DMF-d 7 . IR spectra were recorded on a Perkin Elmer FT-IR 1600 (Perkin Elmer, Waltham, MA, USA).…”
Section: Experimental Procedures Generalmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The graft polymerization from the silsesquioxane backbone is an effective method for transforming the silsesquioxanes into practical and useful materials. [13][14][15][16][17][18][19][20] Grafted silsesquioxanes are expected to show functions based on the incorporated polymeric components without losing the essential properties of the inorganic polysiloxane structure, such as durability against heat and weatherability.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, its structure was refuted later by Frye et al (Frye & Klosowski, 1971) who indicated that the so-called Ph-LPSQ actually was "partially opened polycyclic cages and short-range order but random on large scale". In 2004, Yamamoto et al (Yamamoto et al, 2004) reported an oligomeric polyphenylsilsesquioxane ladder with low ladder regularity. Lately, Brook (Brook, 2000) mentioned that the high Mw ladder polysilsesquioxanes reported are generally random networks, but the ladder structure may be obtained under certain controlled conditions.…”
Section: Synthesis and Characterization Of R-lpsqmentioning
confidence: 99%